ANALISIS PENGEMBANGAN MOTIVASI KARYAWAN PADA SALAH SATU PERUSAHAAN TV BERBASIS LANGGANAN - abdul safrin dg.talli (Fakultas Ekonomi Universitas Indonesia Timur, 2019)
The aimed of this study is to determine the implementation of McClelland motivation theory on the employees of PT. MNC Sky Vision, a branch of Kendari. The subjects in this study are the leaders and employees of PT. MNC Sky Vision. The qualitative analysis is used to analyze the data. The activities in the data analysis consist of reduction, display data, and the data drawing or verification. The obtained data used to test the validity and credibility by triangulation source and triangulation techniques. The results showed that the application of the McClelland motivation theory on the employees of PT. MNC Sky Vision, a branch of Kendari well-implemented. It made a positive impact on the management and employees. To the company management experienced an increase in turnover of 10% annually, and for the employees to have the opportunity to be promoted, earn rewards and additional revenue. The McClelland motivation theory, the most important thing for employees, is a need for achievement. Because it will influence the other necessity.